Affects, economy and politics in the economic practices of peru-vian migrant women in Buenos Aires - Rossi, Emilia; Canevaro, Santiago (Instituto de Altos Estudios Sociales, 2017)
In this article we carry out a comparative analysis of three different political-institutional and working contexts for Peruvian female migrants in Buenos Aires in the last 25 years. We define these contexts based on discontinuities that the women observe in terms of their economic practices and affective relations, taking into account that different policies are relevant in each setting. In the 90s the migration policy was based on Law 23.439, the so-called Videla Law, and the convertibilidad law regulated the economic system. In the decade following the 2001 crisis, social inclusion policies were developed, and in 2013 the domestic service law was approved. In our analysis we refer to the idea of a diverse economy (Gibson-Graham, 2014), which includes heterogeneous economic practices that have to do with material well being and are affected by relations like trust, love, or reciprocity, among others. We show how the different contexts shape the economic practices, particularly the relationship between the economic and the affective spheres, based on the experience of Peruvian migrants who are domestic workers and therefore work in settings where love and affective relations are particularly relevant.